2004
DOI: 10.1007/s00467-004-1551-8
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous epidural hemorrhage in chronic renal failure

Abstract: Spontaneous epidural hemorrhage has been described in a variety of clinical scenarios, including chronic renal failure (CRF). During hemodialysis, patients with CRF rarely develop spinal or cranial epidural hematomas. Such hemorrhages have been attributed to intracranial pressure fluctuations during hemodialysis, heparin administration, uremic-platelet syndrome, or hypertension. Although the exact pathophysiology is not understood, this rare consequence of hemodialysis has been well documented in the literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…Until this date, only 20 cases were documented in the literature. [3][4][5][6]10 Hematologic abnormalities are associated with up to 8% of all intracerebral hemorrhage cases, including anticoagulant-induced coagulopathy. 11 Bleeding events are the most frequent adverse reactions associated with oral anticoagulants.…”
Section: Discussionmentioning
confidence: 99%
“…Until this date, only 20 cases were documented in the literature. [3][4][5][6]10 Hematologic abnormalities are associated with up to 8% of all intracerebral hemorrhage cases, including anticoagulant-induced coagulopathy. 11 Bleeding events are the most frequent adverse reactions associated with oral anticoagulants.…”
Section: Discussionmentioning
confidence: 99%
“…Non-traumatic intracranial extradural hematomas (EDHs) are rare, and reports have associated their etiology with infections [3,9,14,20,25,29,31,33,37], coagulation disorders [39,43], hemodialysis, cardiac surgery [28,38], neoplasms [6,15,18,22,41], and vascular malformations [35]. The first case report of a spontaneous EDH was described in 1951 [37].…”
Section: Introductionmentioning
confidence: 99%
“…Although some investigators found no statistically significant relation, hypertension can be responsible for the development of the SSEH (7,8 (2,3,5,8). But there are several reports in the literature that include conservative treatment (2,3,14).…”
Section: Also In Hemodialysis Patients Intravenous Heparin Adminismentioning
confidence: 99%